Estudo de produtos não agressivos ao meio ambiente para atuar como inibidores de incrustação - Rosa, Katia Regina Silva Alves da (2007)
The present work describes the study on two biomaterials, chitosan and alginic acid, for application as brine scale inhibitor. The activities were started with the study of different matrices for solubilization of the products, following by the evaluation of the products performance as scale inhibitor that embody the study of chemical compatibility with the brine medium and efficiency of static inhibition. Additionally, analyses using physical methods, as IV, RMN and condutimetric titration were carried through to determine the degree of desacetilation of the chitosan that is directly related with its physical properties, such as solubility. Due to low solubility of the chitosan, it was also evaluated the possibility of the use of the chitosan in form of spheres with and without the scale inhibitor impregnation. Chitosan as well as alginic acid, in their basic structures, didn t show up efficient in the performance like scale inhibitor. However, the use of theses products wasn t rejected and it is suggested functionalization reactions to increase their chelation properties, besides exploring the manufacture of chitosan spheres like matrice for systems of control released of scale inhibitors. Key words: scale, scale inhibitors, environment, clean technology, chitos